(untitled) (Jurnal Manajemen dan Kewirausahaan, 2004)
The transition from the 20th to the 21st century in Indonesia has been accompanied by great upheavals in the economic and political sectors as reform efforts to bring about a clean, legitimate democracy which is free from corruption, collusion and nepotism have taken place. These efforts have taken place in order to create a just and prosperous society based on Pancasila and the 1945 Basic Laws. In the areas of both business management and public administration, the function of control and oversight, (first introduced by Fayol and Taylor and developed by other researchers), is used to deal with mistakes, errors, discrepancies, leakages, and cheating so that the operation of activities achieves the objective in accordance with the original planning. Corruption, collusion, and nepotism is everywhere in Indonesia, in fact, to the point that Indonesia has the distinction being one of the countries with the highest level of corruption. Beginning with this condition, the writer has taken the topic of "The Role of Control and Oversight in Corporate Management" to give attention to this issue and seek an answer to the question of how to handle these functions in a corporation. Abstract in Bahasa Indonesia : Pergantian abad XX ke abad XXI di Indonesia ditandai peristiwa-peristiwa besar dalam bidang ekonomi yang semakin terpuruk dan peristiwa-peristiwa besar di bidang politik dalam rangka reformasi sebagai upaya mewujudkan cita-cita pemerintahan menjadi bersih, berwibawa, demokratis bebas dari korupsi, kolusi dan nepotisme (KKN) dalam rangka mencapai masyarakat adil dan makmur berdasarkan Pancasila dan Undang-undang Dasar 1945. Dalam manajemen, baik manajemen bisnis maupun manajemen publik sejak awal diperkenalkan oleh dua tokoh manajemen terkenal yaitu Fayol dan Taylor yang kemudian disusul ilmuwan lain bahwa fungsi pengawasan diharapkan mampu mengatasi adanya kesalahan, penyimpangan, penyelewengan, kebocoran, cacat, kecurangan dan sebagainya sehingga pelaksanaan kegiatan-kegiatan untuk mencapai tujuan yang telah ditetapkan sesuai dengan perencanaan. Korupsi, kolusi, dan mepotisme telah merajalela di Indonesia, bahkan pernah diinformasikan bahwa Indonesia berstatus penyandang gelar sebagai negara yang tingkat korupsinya tinggi. Berangkat dari kondisi ini, penulis mengangkat judul "Fungsi Pengawasan dalam Penyelenggaraan Manajemen Korporasi" sebagai kepedulian dalam memecahkan masalah dan mencari jawaban atas pertanyaan bagaimana cara melaksanakan fungsi dalam suatu korporasi. Kata kunci: fungsi pengawasan, manajemen korporasi.